2014
DOI: 10.1002/pssa.201431315
|View full text |Cite
|
Sign up to set email alerts
|

Forward current enhanced elimination of the radiation induced boron-oxygen complex in silicon n+ -p diodes

Abstract: Using forward current injection with densities in the range 15-30 A/cm 2 we can effectively eliminate the radiation-induced boron-oxygen complex, which is the main compensating center in irradiated Si solar cells. It was found that for a given forward current density the elimination rate is decreasing with increasing irradiation dose. Additionally, some evidences have been obtained on the negative-U properties of the radiationinduced boron-oxygen complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
1
11
1
1
Order By: Relevance
“…) shows that such disappearance actually does occur. Thus, the thermal stability of the defect giving rise to a set of new LVM lines and a partial recovery of the free hole concentration observed upon its annihilation are consistent in general with the similar features observed in deep level transient spectroscopy studies for the B i O i defect .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…) shows that such disappearance actually does occur. Thus, the thermal stability of the defect giving rise to a set of new LVM lines and a partial recovery of the free hole concentration observed upon its annihilation are consistent in general with the similar features observed in deep level transient spectroscopy studies for the B i O i defect .…”
Section: Resultssupporting
confidence: 84%
“…This complex is thought to be responsible for the light‐induced degradation (LID) of some silicon solar cells . However, in spite of its technological importance, the electronic properties, formation, and elimination behavior of the B i O i center have not been understood properly ; local vibrational modes (LVMs) of the defect have not been identified (with an exception of a tentative assignment of an absorption band at 923.5 cm −1 to B i O i given recently in Ref. ), and there is no consensus on its atomic structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies , it was shown by DLTS that the B i C s complexes in boron‐doped Cz‐Si arise synchronously with the dissociation of B i O i defects. The annealing temperature for B i O i , according to the studies is 150–200 °C, i.e., slightly higher than that for B i B s defects observed by us. Taking into account the closeness of these two annealing processes, it can be concluded that B i atoms liberated as a result of the dissociation of both B i B s and B i O i are involved in the formation of B i C s defects in the oxygen‐rich material.…”
Section: Resultscontrasting
confidence: 51%
“…The investigations of the boron‐related radiation defects in Si have been done in the main by deep level transient spectroscopy (DLTS) and electron paramagnetic resonance (EPR) . The main defect appearing in boron‐doped Si under the irradiation is known to be interstitial boron (B i ), which is created through the interaction of a self‐interstitial atom (I) with substitutional boron .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation